266 Breast Cancer in Women Under 30: A Multidisciplinary Approach in a Unique Cohort. (19th August 2022) - Khan, S; Shaker, H; Shrestha, D; Shaw, S; Wilson, R; Abbas, A; Ntanos, I; Williams, K; Wright, C; Absar, MS; Nasir, N
Abstract: Aim: Breast cancer in younger women is relatively rare, tends to be more aggressive and is associated with unique challenges. We sought to examine our practice in managing cancer in patients under 30. Method: A retrospective case-note review was performed on patients under 30 years of age diagnosed with invasive breast through our pathology database since 2007. Clinical and pathological data was collected on patients' cancers, management and follow up as well family history, genetic testing, and fertility management. Results: Forty-five patients were identified. Median age was 28 years (range 20 to 30). Mean tumour size was 30mm (range 4–65mm). Seventeen (38%) of cancers were ER negative, 16 (36%) were HER2 positive. Twenty-three patients (51%) had positive lymph node metastases. SIx patients (13%) had a strong family history and 9 (20%) were BRCA 1 or 2 gene positive. Seven patients (15%) underwent contra-lateral risk-reducing mastectomy. Twenty-5 patients (55%) had no children at diagnosis. Fertility management was discussed with >90% of patients and 12 patients (26%) underwent ovum or embryo preservation. Over a median follow up of 40.5 months (range 4.5 to 128 months), 8 patients (18%) developed local or distant recurrence and 6 patients (13%) died (due to metastasis). Conclusion: In our experience, breast cancer patients under 30 had more aggressive cancers with a relatively high rate of axillary metastases at presentation. Young patients with breast cancer face unique management challenges such as fertility, genetic testing and survivorship issues that are best addressed in a multidisciplinary setting.